Efeito de hidrolisado de peixe sobre o crescimento micelial e controle de Cylindrocladium spathiphylli em espatifilo - Visconti, Alexandre [UNESP]; Bettiol, Wagner; Morandi, Marcelo Augusto Boechat (FapUNIFESP (SciELO), 2010)
Fish hydrolyzed (HP), poultry manure (CF), shrimp skin (CC), cattle manure (EB), sewage sludge (LE) and castorbean presscake (TM) were evaluated for their effect of aqueous extracts with and without autoclaving, on mycelial growth and conidial germination of Cylindrocladium spathiphylli. The effect of mixtures of residues with potting mixes and their volatile compounds were also evaluated on the mycelial growth of the pathogen. To evaluate the effect of HP in the suppressiveness to Cylindrocladium spathiphylli, HP was added in potting mix artificially infested, at concentrations of 0, 10, 20, 30, 40 and 50% of the volume of water required to reach the water retention capacity of the potting mix. The mixtures were incubated for 10 days and transferred to pots containing one plug of Spathiphyllum Opal per pot. In the experiments in vitro, aqueous extracts and mixtures containing HP showed the highest suppressiveness against the pathogen. In the Spathiphyllum growing, the suppressiveness occurred at concentrations higher than 20% of fish hidrolyzed.
Effect of fish hydrolyzed on mycelial growth and control of Cylindrocladium spathiphylli in Spathiphyllum
Keywords: Cylindrocladium spathiphylli; Fish hydrolysed; Organic matter; Suppressiveness; Bos; Calonectria spathiphylli; Decapoda (Crustacea); Ricinus communis; Spathiphyllum